Epidemiological investigation of norovirus infections in Punjab, Pakistan, through the One Health approach - Yasir, Ammar; Mahmood, Yasir; Yaqoob, Muhammad Arsalan; Zia, Ubaid-ur-Rehman; Munoz-Zanzi, Claudia; Alam, Muhammad Masroor; Warraich, Muhammad Akib; Hassan Mushtaq, Muhammad (Frontiers in Public Health, 2023)
Norovirus mainly associated with acute gastroenteritis is very contagious and can affect a vast range of species ranging from cattle, pigs, dogs, mice, cats, sheep, and lions to humans. It is a foodborne pathogen that mainly transmits through the fecal-oral route. This is the first-ever study conducted in the Lahore and Sheikhupura Districts of Punjab Pakistan to investigate noroviruses through a One Health approach. From January 2020 to September 2021, 200 fecal samples were collected from clinical cases of hospitalized patients and 200 fecal samples from sick animals at veterinary hospitals and local farms. Additionally, 500 food and beverage samples were collected from street vendors and retail stores. A predesigned questionnaire was used to assess the risk factors and clinical characteristics of sick people and animals. Overall, 14% of the human clinical samples were positive by RT-PCR for genogroup GII. All bovine samples were negative. Food and beverage samples were tested in pools resulting in sugarcane juice samples positive for genogroup GII. The previous contact of the patient with acute gastroenteritis patient, sex, and presence of vomiting were found to be significant risk factors (p≤0.05). A substantial number of diarrhea cases associated with noroviruses, calls for additional studies to investigate the epidemiology, and transmission, and improve surveillance.